Social Dimensions of Defense Policy: Tensions between National Consciousness and Liberal Democratic Values - Terbish, Bilguun (Mongolian Journal of Strategic Studies, 2025)
This article examines the influence of progressive liberal discourse emerging in Mongolian society, seeking to identify the challenges it poses to national identity, collective consciousness, and traditional values. The analysis brings together classical and contemporary sociological theories with critiques from political realism, drawing in particular on Durkheim’s concept of collective con science, Foucault’s concept of discourse, Bourdieu’s theory of symbolic power, and Buzan’s notion of societal security. Methodologically, the analysis relies on Norman Fairclough’s critical discourse analysis and incorporates publicly available documents, online sources, and interview data from civil society organizations engaged in youth-oriented activities in Mongolia. Within this framework, the study identifies challenges related to social cohesion, cultural continuity, national security, and defense policy. It demonstrates that attempts to localize the values of progressive liberalism come into fundamental conflict with traditional values, gradually weakining social trust, collective con sciousness, and the resilience of national identity. Батлан хамгаалах бодлогын нийгмийн чиглэл: Үндэсний ухамсар ба либерал-ардчилсан үнэт зүйлсийн зөрчилдөөн Хураангуй: Энэхүү өгүүлэл нь Монголын нийгэмд түгэн дэлгэрч буй прогрессив либерал дискурсын нөлөөг авч үзсэн бөгөөд үндэсний ижилсэл, хамтын ухамсар, уламжлалт үнэт зүйлсэд учруулж буй сорилтыг тодорхойлох зорилготой. Тус өгүүлэлд социологийн сонгодог ба орчин үеийн онолууд, улс төрийн реализмын шүүмжлэлийг хослуулан ашигласан бөгөөд ялангуяа Дюркгеймийн хамтын ухамсар, Фукргийн дискурс, Бурдьегийн симбволик эрх мэдэл, Бузаны нийгмийн аюулгүй байдлын онолын ойлголтуудыг тулгуур болгон ашигласан. Арга зүйн хувьд Норман Фэйрклофийн шүүмжлэлт дискурс шинжилгээнд тулгуурлан Монголын залуучууд руу чиглэсэн үйл ажиллагаа эрхэлдэг иргэний нийгмийн байгууллагуудын нийтэд нээлттэй баримт бичиг, цахим эх сурвалж болон ярилцлагын өгөгдлийг хамруулсан. Шинжилгээний хүрээнд нийгмийн эв нэгдэл, соёлын залгамж чанарын ач холбогдол, аюулгүй байдал болон батлан хамгаалах бодлогод үүсэж буй асуудлыг дурдсан бөгөөд прогрессив либерализмын үнэт зүйлсийг нутагшуулах оролдлого нь уламжлалт үнэт зүйлстэй үндсээрээ зөрчилдөж, нийгмийн итгэлцэл, хамтын ухамсар, үндэсний үзлийн дархлааг алгуур сулруулж буй эсэхийг тодруулав. Түлхүүр үг: Үндэсний ижилсэл, хамтын ухамсар, батлан хамгаалах бодлого, либерал прогрессивизм, символик эрх мэдэл